Utilisation of modern contraceptive among women of childbearing age in resource constraint setting: evidence from 2008 national demographic and health survey in Nigeria (2014)
Nigerian women are known to have high fertility rates and a low utilization of modern contraceptives. Understanding the factors affecting the use of contraceptives using a nationally representative data is crucial to tackling the low prevalence of contraceptive use in Nigeria. Methods: Secondary dataset of 33,385 women aged 15-49 years, who participated in the 2008 National Demographic and Health Survey was analysed. We calculated contraceptive prevalence rates for various population sub-groups, and examined the association between socio-demographic characteristics and current modern contraceptive use, using multiple logistic regressions. Results: Mean age of the respondents was 31.1±8.8 years. Current contraceptive prevalence rate was 13.2%, while that of modern methods was 9.4%. The significant factors associated with the utilization of contraceptives were urban residence (OR=1.22, 95%CI=1.11-1.35), being a working class woman (OR=1.22, 95%CI=1.11-1.35), being educated (OR=1.22, 95%CI=1.11-1.35), parity (OR=1.22, 95%CI=1.11-1.35), being wealthy (OR=2.62, 95%CI=2.14-3.21). Importantly, the likelihood utilization varied across the gradient of wealth. Women in richest (OR=2.62, 95%CI=2.14-3.21), richer (OR=2.44, 95%CI=2 .02-2.94), and middle (OR=1.78, 95%CI=1.48-2.14) wealth quintiles were more likely to use modern method compared to women in the poorest category. Conclusions: Prevalence rates were very low across virtually all segments of the population. Concerted efforts are required to increase use of modern methods of contraception.